Analysis of Household Income of Capture Fisheries Business in Indonesia - Silviana Taniu; Dyah Wulan Sari; Dias Satria; Tri Haryanto; Amirusholihin Amirusholihin (Agriekonomika, 2023)
This study aims to analyze the household income of capture fisheries business actors in Indonesia. The data used is the latest data from the Indonesian Agricultural Sector Household Income Survey collected in 2014 by the Central Bureau of Statistics. Specifically, this study uses datasets from 28,727 fisher households spread across 33 provinces. By using the OLS regression, this study found that apart from the age of the head of the household, education level of the head of the household, and household size, it can be concluded that capture fisheries households that are members of Kelompok Usaha Bersama/KUB, members of cooperative, access formal credit, easily market fish, and receive grants from the government, these households tend to have higher incomes.